Effect of Microvascular Decompression of the Vagus Root Entry/Exit Zone on Blood Pressure in Patients with Hemifacial Spasm Associated with Essential Hypertension: A Retrospective Clinical Analysis - Wei, Xuefeng; Wang, Jiao; Kong, Xuerui; Gao, Caibin; Wang, Feng (Journal of Neurological Surgery Part B: Skull Base, 2021)
Background This study aimed to evaluate blood pressure alterations after microvascular decompression (MVD) surgery in patients with hemifacial spasm (HFS) with coexisting hypertension (HTN).Methods A total of 56 patients with HFS with concurrent HTN who underwent MVD surgery in our center between 2015 and 2019 were retrospectively analyzed. Patients were divided into control and experimental groups: patients who received MVD treatment for only the facial nerve and those who received MVD for the affected facial nerve, ipsilateral vagus nerve, and adjacent ventrolateral medulla, respectively. Preoperative (3 days) and postoperative (7 days and 6 months) blood pressure measurements were analyzed.Results No statistically significant differences were observed in gender, age, HFS course, HTN course, HTN grade, and preoperative blood pressure between the two groups. No significant difference was observed between pre- and postoperative blood pressure in the control group. In the experimental group, systolic blood pressure significantly differed between 3 preoperative days and 7 postoperative days (p < 0.05), as did diastolic blood pressure (p < 0.05). Measurement at 6 postoperative months also showed significant differences for both systolic blood pressure and diastolic blood pressure compared with that at 3 preoperative days (p < 0.05). HTN grade according to the World Health Organization classification criteria significantly differed between preoperative and postoperative measurements (p < 0.05).Conclusion Vascular decompression of the ipsilateral vagus nerve roots may improve blood pressure management in patients with HFS with coexisting HTN who undergo MVD. Laterality of involvement (left vs. right) did not significantly differ.
Keywords: hemifacial spasm; microvascular decompression; vagus nerve root; hypertension